Pengaruh penggunaan media rosetta stone untuk mengembangkan ketrampilan menyimak : Penelitian - Muhammad Rondi; Faruq Abdul Muid (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2021)
This study aims to determine the influence of rosetta stone media to improve listening skills in language leasson. The type of research is quantitative research which data analysis carried out using the Ttest formula. This study placed at MI Nurul Ulum Bulu Sugihwaras Bojonegoro and the students at that school as a sample of research. The results showed that the use of rosetta stone had a significant influence because the results of the Ttest showed that Tt < To = (-50.328) with a significance level (2-Tailed) of 0.000 < 0.005. then Ho was rejected and Ha was accepted. Using Rosetta stone in language lesson is very effective in improving listening skills of MI Nurul Ulum Bulu Sugihwaras Bojonegoro students.